The Relationship Between Smartphone Addiction and Interpersonal Communication among Preclinical Students at the School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia - Margaret Clarissa Gunawan; Lenny Gustaman (Journal of Urban Health Research, 2022)
Introduction: The high number of smartphone usage throughout the world, including in Indonesia, can increase the likelihood of someone experiencing smartphone dependency. One impact of smartphone addiction is the decline in face-to-face interpersonal communication. Methods: The design of this study was analytic descriptive with a cross-sectional approach involving preclinical students at the School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, who met the inclusion and exclusion criteria. Data was collected using the Smartphone Addiction Scale Short Version (SAS-SV) and the interpersonal communication scale questionnaire. Results: From a total of 135 respondents, it was found that there was a significant relationship between smartphone addiction and interpersonal communication, with a p-value of 0.029 (<0.05). Conclusions: Smartphone addiction has a significant influence on interpersonal communication